Alpha-type phospholipase A(2) inhibitors from snake blood - Santos-Filho, Norival A. [UNESP] (2017)
it is of popular and scientific knowledge that toxins from snake venom ( among them the PLA(2) and myotoxins) are neutralized by various compounds, such as antibodies and proteins purified from animal blood. Venomous and nonvenomous snakes have PLA2 inhibitory proteins, called PLIs, in their blood serum. One hypothesis that could explain the presence of these PLIs in the serum of venomous snakes would be self-protection against the enzymes of their own venom, which eventually could reach the circulatory system. However, the presence of PLIs in nonvenomous snakes suggests that their physiological role might not be restricted to protection against PLA2 toxins, but could be extended to other functions, as in the innate immune system and local regulation of PLA(2)s. The present study aimed to review the currently available literature on PLA2 and myotoxin alpha inhibitors present in snake plasma, thus helping to improve the research on these molecules. Furthermore, this review includes current information regarding the mechanism of action of these inhibitors in an attempt to better understand their application, and proposes the use of these molecules as new models in snakebite therapy. These molecules may help in the neutralization of different types of phospholipases A(2) and myotoxins, complementing the conventional serum therapy.